2012
DOI: 10.1111/j.1439-0531.2012.02057.x
|View full text |Cite
|
Sign up to set email alerts
|

Livestock Induced Pluripotent Stem Cells

Abstract: ContentsChimeric animals generated from livestock-induced pluripotent stem cells (iPSCs) have opened the door of opportunity to genetically manipulate species for the production of biomedical models, improving traits of agricultural importance and potentially providing a system to test novel iPSC therapies. The potential of pluripotent stem cells in livestock has long been recognized, with many attempts being chronicled to isolate, culture and characterize pluripotent cells from embryos. However, in most cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Embryonic stem cells and iPSC technologies are also explored for utilization in livestock research, breeding, and transgenesis with a special focus on bovine and porcine cells. Pluripotent cells may be used to improve traits of agricultural importance, genetically manipulate species for the production of biomedical models, and potentially provide a model to test novel iPSC therapies [Lu et al 2012]. However, it remains a challenging task to derive and culture stable pluripotent cell lines from large domestic animals [Ezashi et al 2012;Telugu et al 2010].…”
Section: Introductionmentioning
confidence: 99%
“…Embryonic stem cells and iPSC technologies are also explored for utilization in livestock research, breeding, and transgenesis with a special focus on bovine and porcine cells. Pluripotent cells may be used to improve traits of agricultural importance, genetically manipulate species for the production of biomedical models, and potentially provide a model to test novel iPSC therapies [Lu et al 2012]. However, it remains a challenging task to derive and culture stable pluripotent cell lines from large domestic animals [Ezashi et al 2012;Telugu et al 2010].…”
Section: Introductionmentioning
confidence: 99%
“…iPSCs can be utilized to generate animals with unique genetic and epigenetic traits as they can form germline competent chimeric animals and ultimately offspring with the specified phenotypes [9, 10]. iPSC technology has been successfully applied to mammalian species, including humans [912], and it has garnered success with avian species as well, such as chickens and quails [13–15]. Chicken induced pluripotent stem cells (ciPSCs) display characteristics indicative of a stem cell state including morphological and functional characteristic [13, 14, 16].…”
Section: Introductionmentioning
confidence: 99%
“…As the most stringent proof of pluripotency, ciPSCs can be used to generate chimeric birds by transplantation into the embryo at early stages of embryogenesis, as shown with chicken-quails and chicken-chicken chimeras [13, 14]. Chimeric animals can then be bred to produce offspring with specific traits, as demonstrated by our group in other livestock species [15, 18]. Further, our laboratory has demonstrated that ciPSCs can undergo in vitro differentiation into early primordial germ cells (PGCs), which are capable of migrating to the gonads when injected into a developing embryo [19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that PRMT5 combined with KLF4 and OCT3/4 reprogrammed mouse somatic cells to a state indistinguishable from ES cells, in terms of their gene expression profile, DNA methylation status, capacity to differentiate into the three germ layers and germline transmission . However, there has been lack of information concerning PRMT5 expression profile and its effects on somatic cell reprogramming in livestock . Dairy goats have a relatively short period of gestation and provide milk, meat, fur and other valuable products; also they can be used as animal models for biomedical research in production of peptides, using transgenic animals .…”
Section: Introductionmentioning
confidence: 99%